Cortical Inactivation Does Not Block Response Enhancement in the Superior Colliculus - Kordecka, Katarzyna; Foik, Andrzej T.; Wierzbicka, Agnieszka; Waleszczyk, Wioletta J. (Frontiers in Systems Neuroscience, 2020)
Repetitive visual stimulation is successfully used in a study on the visual evoked potential (VEP) plasticity in the visual system in mammals. Practicing visual tasks or repeated exposure to sensory stimuli can induce neuronal network changes in the cortical circuits and improve the perception of these stimuli. However little is known about the effect of visual training at the subcortical level. In the present study, we extend the knowledge showing positive results of this training in the rat’s Superior colliculus (SC). In electrophysiological experiments, we showed that a single training session lasting several hours induces a response enhancement both in the primary visual cortex (V1) and in the SC. Further, we tested if collicular responses will be enhanced without V1 input. For this reason, we inactivated the V1 by applying xylocaine solution onto the cortical surface during visual training. Our results revealed that SC’s response enhancement was present even without V1 inputs and showed no difference in amplitude comparing to VEPs enhancement while the V1 was active. These data suggest that the visual system plasticity and facilitation can develop independently but simultaneously in different parts of the visual system.